Húmus: design para a sustentabilidade na tatuagem - Ramos, Patrick Bernardi (My University, 2024)
The growing number of issues related to sustainability in society affects many segments that previously did not discuss the topic. In the field of tattooing, the concern with the environmental impact caused by this activity is generating a debate about the best means and materials to carry out this process. Professionals and clients seek solutions that are in line with the best sustainable practices. Therefore, this work aims to develop a brand, service and product project that facilitates sustainability in this market so that the public involved in tattooing has adequate solutions to solve their demands, while not negatively impacting the environment with old practices. of that segment. In order to propose solutions to the problem, the Design Thinking methodology combined with Life Cycle Design was used. The result was the development of a brand-product-service system that sought to facilitate the tattoo segment to become more sustainable, using support: ecological products (Butter for Tattoos and Natural Aftercare); a service that aims to disseminate sustainable services for professionals to adapt their studios; introduce sustainable studios to new audiences; encourage a community of tattoo artists and tattooed people who are aware and concerned about the environment and the impact of the actions we take when getting a tattoo; and a brand with which the public can identify. [resumo fornecido pelo autor]
O número crescente de temas relacionados a sustentabilidade na sociedade atinge muitos segmentos que antes não discutiam sobre o tema. No ramo da tatuagem, a preocupação com o impacto ambiental que causa essa atividade está gerando um debate sobre os melhores meios e materiais para se realizar esse processo. Profissionais e clientes buscam soluções que estejam alinhadas com as melhores práticas sustentáveis. Portanto, este trabalho tem como objetivo desenvolver um projeto de marca, serviço e produto que facilite a sustentabilidade nesse mercado para que os públicos envolvidos na tatuagem tenham soluções adequadas para resolver suas demandas, ao mesmo tempo que não impactem negativamente o meio ambiente com práticas antigas desse segmento. A fim de propor soluções para o problema, foi empregada a metodologia do Design Thinking aliada ao Life Cycle Design. O resultado foi o desenvolvimento de um sistema marca-produto-serviço que buscou facilitar o segmento da tatuagem a se tornar mais sustentável, utilizando o suporte: produtos ecológicos (Manteiga para Tatuagem e Aftercare Natural); um serviço que tem por objetivo divulgar serviços sustentáveis para profissionais adequarem os seus estúdios; apresentar estúdios sustentáveis para novos públicos; estimular uma comunidade de tatuadores e tatuados conscientes e preocupados com o meio ambiente e o impacto das ações que tomamos na hora de realizar uma tatuagem; e uma marca com a qual o público se identifique. [resumo fornecido pelo autor]
Keywords: Projeto de produto; Sustentabilidade; Tatuagem; Meio ambiente; Produtos ecológicos